Incorporação de ativos cosméticos em matrizes inorgãnicas mesoporosas - Ortiz, Giovanna Canalli [UNIFESP] (2015)
To develop innovative products that provide better stability termal/chemical and performance of it?s constituents has raised the interest of the cosmetic companies. These companies have interest in numerous active ingredients and particularly in antioxidants species. Antioxidants that are worth mentioning are rich in polyphenols such as the widely studied grape seed extract, that contains a high content of these species and it is shown to be very promising in the field of active ingredients for production of cosmetics, especially as anti-aging. An important point to be discussed is that grape seed extract has a serious stability problem because it is very hygroscopic and is easily degraded; likewise fragrances, which are very volatile materials. So, to try to solve this problem, this project aimed to incorporate two raw materials (grape seed extract and cotton fragrance) in an inorganic matrix (SBA-15) in order to create differentiated materials. The materials were prepared using the wet impregnation method, using as solvent ethanol or a mixture of ethanol / toluene. The characterization was carried out by SAXS (small angle x ray scattering), NAI (nitrogen adsorption/ desorption), TG (thermogravimetry), FT-IR (Fourier transform infrared spectroscopy) and SEM (scanning electron microscopy). The results of TG and NAI indicated that the use of the solvent mixture (ethanol / toluene) is more suitable for the incorporation of grape seed extract to SBA-15, since the final material contains a larger quantity of this active ingredient. On the other hand, for fragrance, the best solvent was ethanol. For both actives an improvement in thermal stability was observed. From the SAXS data, it was found that there were no significant shifts of the peaks corresponding to the reflection characteristics of a hexagonal mesoporous structure as SBA-15. The FT-IR and SEM data corroborated with other techniques, where it was found that the materials were prepared successfully without damage to the matrix, indicating the presence of active ingredients in the pores of SBA-15.